Two cases of low-grade appendiceal mucinous neoplasm (LAMN) mimicking ovarian tumors successfully treated with laparoscopic surgery - Anjo, Kazuki; Yazawa, Hiroyuki; Ojima, Tsukasa Sanpei; Yazawa, Riho; Inazuki, Akari (FUKUSHIMA JOURNAL OF MEDICAL SCIENCE, 2025)
We report two cases of low-grade appendiceal mucinous neoplasm (LAMN) mimicking ovarian tumors that were treated with laparoscopic surgery. Case 1: A 57-year-old woman was referred to our hospital because of a pelvic mass noted during physical examination. Imaging revealed an oval, cystic, 81×39-mm mass diagnosed as a right ovarian tumor, and surgery was performed. Intraoperative findings revealed an appendiceal tumor, and laparoscopic appendectomy was conducted. The pathological diagnosis was LAMN.Case 2: A 76-year-old woman was referred to our hospital because of a pelvic mass noted during physical examination. Imaging revealed an oval, cystic, 36×23-mm mass in the pelvic cavity, which was suspected to be a right ovarian tumor. Since it was slightly displaced to the cephalic side, surgery was performed with the possibility of a gastrointestinal tumor in mind. Intraoperative findings revealed an appendiceal tumor, and a laparoscopic appendectomy was conducted. The pathological diagnosis was LAMN.LAMN is a rare lesion with a risk of serious complications if the appendiceal wall ruptures and the tumor extends beyond the appendix. Although its preoperative diagnosis is challenging, it is important that gynecologists differentiate it from adnexal tumors.